2018
DOI: 10.1007/s00264-018-4100-y
|View full text |Cite
|
Sign up to set email alerts
|

Defining growth potential and barriers to same day discharge total knee arthroplasty

Abstract: Outpatient TKA is safe in selected patients, and inclusion can likely be broadened by addressing modifiable exclusions and narrowing medical exclusions. We found that 55% of our TKA population could be appropriate for outpatient surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…23 While database studies have shown conflicting results, other studies have shown similar risk of adverse events and readmissions when patient selection is narrowed to include only younger and healthier patients. 14,20,[25][26][27] Although these studies reported a similar risk of adverse events and complications, it is important to note the strict selection criteria used by in these studies. To select a healthy cohort of patients, patients with a history of diabetes mellitus, myocardial infarction, stroke, congestive heart failure, deep venous thromboembolism, pulmonary embolism, cardiac arrhythmia, respiratory failure, chronic pain requiring regular opioid medications, active cardiopulmonary disease, history of sleep apnea, active anticoagulation therapy, and significant obesity were all excluded.…”
Section: Risks Of Outpatient Tkamentioning
confidence: 96%
See 1 more Smart Citation
“…23 While database studies have shown conflicting results, other studies have shown similar risk of adverse events and readmissions when patient selection is narrowed to include only younger and healthier patients. 14,20,[25][26][27] Although these studies reported a similar risk of adverse events and complications, it is important to note the strict selection criteria used by in these studies. To select a healthy cohort of patients, patients with a history of diabetes mellitus, myocardial infarction, stroke, congestive heart failure, deep venous thromboembolism, pulmonary embolism, cardiac arrhythmia, respiratory failure, chronic pain requiring regular opioid medications, active cardiopulmonary disease, history of sleep apnea, active anticoagulation therapy, and significant obesity were all excluded.…”
Section: Risks Of Outpatient Tkamentioning
confidence: 96%
“…23,24 Many surgeons would acknowledge that a significant number of patients are not candidates for OP TKA, so the development of consistent selection criteria is critical as pressures increase to eliminate a hospital stay after TKA. 14,20,25,26,28…”
Section: Outcomes Of Outpatient Tkamentioning
confidence: 99%
“…Some authors suggested that no differences exist in terms of complication rate between outpatient TKAs and inpatient TKAs. The retrospective studies of Darrith et al [25] on 92 patients (46 outpatients), Cassard et al [24] on 574 patients (61 outpatients), Springer et al [29] on 166 patients (92 outpatients), and Gillis et al [27] on 400 patients (125 outpatients), as well as the prospective comparative cohort study of Gauthier-Kwan et al [26] on 43 outpatients vs 43 inpatients TKAs, reported comparable complication and readmission rates. A comparable readmission rate was also reported by Kimball et al [30] in a retrospective study analyzing 1726 patients (863 outpatients).…”
Section: Discussionmentioning
confidence: 93%
“…Eleven of these studies were excluded after full-text reading for the following reasons: 2 studies had results non-separated from other joints; 7 studies had data coming from the same database of other articles and included a lower number of patients; 1 study reported complications and readmission as odds ratio, 1 study reported data as percentage of subgroups making the results inaccurate for the analysis [22]. For this reasons, only 8 articles were included in the meta-analysis [23][24][25][26][27][28][29][30] (Fig. 1).…”
Section: Review Statisticsmentioning
confidence: 99%
“…As many as 55% of current patients hospitalized postoperatively may be eligible for same-day discharge. 2 Patients endorsed same-day discharge 87% of the time, 3 and complication r a t e s w e r e c o m p a r a b l e b e t w e e n patients who were discharged the same day and those who remained in hospital. 4,5 Finally, system cost saving was estimated at 32.7%.…”
mentioning
confidence: 99%